Modulation of Muscle Fiber Compositions in Response to Hypoxia via Pyruvate Dehydrogenase Kinase-1 - Nguyen, Daniel D.; Kim, Gyuyoup; Pae, Eung-Kwon (Frontiers in Physiology, 2016)
Muscle fiber-type changes in hypoxic conditions in accordance with pyruvate dehydrogenase kinase (Pdk)-1 and hypoxia inducible factor (Hif)-1α were investigated in rats. Hif-1α and its down-stream molecule Pdk-1 are well known for readily response to hypoxia. We questioned their roles in relation to changes in myosin heavy chain (MyHC) composition in skeletal muscles. We hypothesize that the level of Pdk-1 with respect to the level of Hif-1α determines MyHC composition of the muscle in rats in hypoxia. Young male rats were housed in a chamber maintained at 11.5% (for sustained hypoxia) or fluctuating between 11.5% and 20.8% (for intermittent hypoxia or IH) oxygen levels. Then, muscle tissues from the geniohyoid (GH), soleus, and anterior tibialis (TA) were obtained at the end of hypoxic conditionings. After both hypoxic conditionings, protein levels of Pdk-1 and Hif-1 increased in GH muscles. GH muscles in acute sustained hypoxia favor an anaerobic glycolytic pathway, resulting in an increase in glycolytic MyHC IIb protein-rich fibers while maintain original fatigue-resistant MyHC IIa protein in the fibers; thus, the numbers of IIa- and IIb MyHC co-expressing fibers increased. Exogenous Pdk-1 over-expression using plasmid vectors elevated not only the glycolytic MyHC IIb, but also IIx as well as IIa expressions in C2C12 myotubes in ambient air significantly. The increase of dual expression of IIa- and IIb MyHC proteins in fibers harvested from the geniohyoid muscle has a potential to improve endurance as shown in our fatigability tests. By increasing the Pdk-1/Hif-1 ratio, a mixed-type muscle could alter endurance within the innate characteristics of the muscle toward more fatigue resistant. We conclude that an increased Pdk-1 level in skeletal muscle helps maintain MyHC compositions to be a fatigue resistant mixed-type muscle.